2018
DOI: 10.18805/ijar.b-3468
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genetic variability of Alpha Casein gene, CSN1S1 in Bikaneri camel (Camelus dromedarius) milk

Abstract: Camel milk is an important protein source for the nomadic communities living in the arid lands of the world, In recent years there has been an increase in consumption of non-bovine milk as an alternative protein source for humans. Camel milk seems to be containing larger amount of total proteins, such as lactoferrin and immunoglobulins as compared to the cow milk, which may be responsible for the better antimicrobial properties. The casein fraction of milk proteins consists of four caseins, namely s1-casein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As in cow milk ca. 80% of the total protein fraction of camel milk is represented by caseins (CN), consisting of a s1 -, a s2 -, b-, c-, and j-CN (Erhardt et al 2016;Ryskaliyeva et al 2018;Singh et al 2018), as well as a b-CN short isoform (Ryskaliyeva et al 2018). Whereas band j-CN were monomorphic, three different genetic variants (A, C and D) were identified in the a s1 -CNs (Erhardt et al 2016).…”
Section: Milk Proteins and Related Genesmentioning
confidence: 99%
“…As in cow milk ca. 80% of the total protein fraction of camel milk is represented by caseins (CN), consisting of a s1 -, a s2 -, b-, c-, and j-CN (Erhardt et al 2016;Ryskaliyeva et al 2018;Singh et al 2018), as well as a b-CN short isoform (Ryskaliyeva et al 2018). Whereas band j-CN were monomorphic, three different genetic variants (A, C and D) were identified in the a s1 -CNs (Erhardt et al 2016).…”
Section: Milk Proteins and Related Genesmentioning
confidence: 99%
“…Bactrian camels feature two humps on their backs and are adapted to live in desert areas (Bai et al 2020). Studies have proved that camel milk has antioxidant, anti-infection, anti-diabetes, anti-cancer and anti-hypertensive effects (Sharma et al 2022;Singh et al 2019). Studies have found that camel milk has the effects of lowering blood sugar and IR and can be used as an adjuvant in the treatment of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…CMP health benefits have been studied worldwide for three decades. Biochemical investigations show that insulin-like protein, lactoferrin and immunoglobulins provide CMP scientific value (Agrawal et al, 2013;Singh et al, 2019). CMP is a powerful bioactive for use as antidiabetic drugs (Anwar et al 2022).…”
Section: Introductionmentioning
confidence: 99%